2012
DOI: 10.1021/jp3004135
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Nonadiabatic Effects of the Endohedral Clusters X@Al12 (X = B, C, N, Al, Si, P) with 39, 40, and 41 Valence Electrons

Abstract: Metallic nanoclusters, with one electron or hole difference from closed shell, might end up in a degenerate state undergoing a Jahn–Teller distortion as a result of nonadiabatic effects, which are a manifestation of the electron–vibron coupling. Here, we report a theoretical study on the stability and nonadiabaticity of the neutral and charged endohedral clusters X@Al12 (X = B, C, N, Al, Si, P) around icosahedral symmetry, for 39, 40, and 41 valence electrons. The nonadiabatic effects are evaluated through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…All the geometries were optimized without any symmetry constraint. We have considered only endohedral doped Al icosahedral clusters since previous theoretical studies have reported that the endohedral doping is energetically more favorable than the exohedral doping 30 , 31 . The Al 13 and BAl 12 both have 39 valence electrons with electronic configuration of 1S 2 1P 6 1D 10 2S 2 1F 14 2 P 5 .…”
Section: Resultsmentioning
confidence: 99%
“…All the geometries were optimized without any symmetry constraint. We have considered only endohedral doped Al icosahedral clusters since previous theoretical studies have reported that the endohedral doping is energetically more favorable than the exohedral doping 30 , 31 . The Al 13 and BAl 12 both have 39 valence electrons with electronic configuration of 1S 2 1P 6 1D 10 2S 2 1F 14 2 P 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The power of prediction of these methods have been previously tested for the hexasilabenzene molecule [25]. We followed the method developed by Molina et al [29] to estimate the JahnTeller energy gain (EJT). In order to determine the coupling of the ground state with some excited state, singlet to singlet electronic transitions for the first seventy excited states were evaluated for the D 2h Si 10 H 8 cluster using TDDFT with ZORA scalar and all electron TZ2P basis.…”
Section: Methodsmentioning
confidence: 99%
“…Soto and coworkers evaluated the series of endohedral clusters involving the icosahedral Al 12 cage, of the form X@Al 12 (X = B, C, N, Al, Si, P) leading to 39, 40, and 41 valence electrons, which are one electron or hole clusters related to the closed shell 1S 2 1P 6 1D 10 2S 2 2P 6 Al 13 − superatom. This open‐shell configuration for 39 and 41 electrons, results in a partially filled degenerate state which in turn undergoes a Jahn–Teller distortion with an ellipsoidal departure from the spherical.…”
Section: Bare Superatomsmentioning
confidence: 99%
“…It is important to stress that besides the favorable electronic structure and geometrical shape, further analysis of possible isomers should be carried out to pursue energy minima geometries. [51] Soto and coworkers [52,53] [54] Their results indicate the relevance of keeping the dopant atom lying on the cluster surface, and thus, further efforts in the characterization of cage doped clusters should be pertinent in catalytic application, in addition to endohedral doping.…”
mentioning
confidence: 99%